Los orígenes del poder episcopal sobre la ciudad de Oviedo en la Edad Media - Ruiz de la Peña Solar, Juan Ignacio; Beltrán Suárez, Soledad (En la España Medieval, 2007)
Episcopal rights and jurisdiction over Oviedo during the thirteenth century (“episcopal third”). Their twelfth-century origins. Distinction between the old civitas, affected by episcopal jurisdiction, and the urban expansion or villa. Topographical description of the principal architectonic elements of the civitas. The development of double jurisdiction, royal and episcopal, over Oviedo.